EFFICACY OF FEAR APPEALS ON ADOPTION OF COVID-19 PREVENTIVE MEASURES: A CASE OF BODA BODA RIDERS IN NAIROBI COUNTY, KENYA - Kigatiira, Kinya Kathure (International Journal of Research -GRANTHAALAYAH, 2020)
This study was an investigation of the effectiveness of fear appeals on the adoption of COVID-19 preventive measures among boda boda riders in the Nairobi County, Kenya. The problem of the study was that little or no research has been conducted on fear appeals and adoption of COVID-19 preventive measures, hence a gap that demands specific studies to be undertaken to fill it. This study draws from the Health Belief Model (HBM). Case study research design was used because the study focused only on boda boda riders operating in the seventeen constituencies in Nairobi County. Convenience sampling was used to identify the riders who were available and willing to participate in the study. The main data collection tool was telephone interviews. Findings of this study revealed that fear appeals were effective in making boda boda riders in Nairobi County adopt the COVID-19 preventive measures. The boda boda riders’ felt that they were susceptible to the coronavirus disease, police arrests, fourteen days mandatory quarantine, motorcycles being impounded and payment of fines, if they did not adopt the COVID-19 preventive measures. Moreover, the riders believed that the virus posed a more serious threat to their health and lives. The operators perceived susceptibility to the threats, elicited high levels of fear. The COVID-19 preventive measures, also, provided the riders with an effective method of changing behavior which they believe will protect them from contracting the virus. This study recommended that in order to motivate the boda boda riders to continue practicing the COVID-19 preventive measures, the government should frequently give the riders masks and hand sanitizers. Further, more communication campaigns should be developed and conducted on COVID-19 awareness and prevention among boda boda riders.